Regional variation in high vowel deletion in New Brunswick French: Preliminary observations - Cichocki, Wladyslaw (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2023)
This paper presents findings of a descriptive study that suggest that the deletion of high vowels, a process that is generally associated with Laurentian French, may have begun to spread across francophone regions of New Brunswick. The study examines the pronunciation of /t, d/ + /i, y/ sequences in a small number of lexical items, with a focus on vowel deletion. Based on acoustic phonetic analyses of sentences read by 136 speakers from the five main French-speaking regions in New Brunswick, results indicate that /i, y/ deletion rates are relatively high in the NorthWest, a region that is located adjacent to Quebec, but lower in other regions, with the lowest rates occurring in the SouthEast. Deletion rates are significantly higher among younger speakers than older speakers, indicating that this may be a sound change in progress. The results highlight an interaction between high vowel deletion and /t, d/ affrication. These preliminary observations provide guidelines for future dialectological and phonetic research on this process.